ANALISIS KINERJA DINAS PASAR DALAM MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PENGELOLAAN SISTEM AKUNTANSI RETRIBUSI PASAR (Studi Empiris pada Dinas Pasar Kota Semarang) - Intan Faria Rohyati; Hardi Winoto (Universitas Muhammadiyah Semarang, 2012)
The purposeof this study is to analyze the level of efficiency and effectiveness of market acceptance of retribution, to analyze the performance of the market acceptance, along with analyzing the suitability of recording and reporting on financial SKPD in the city of Semarang, Particulary Semarang Office Market with Permendagri No. 13 of 2006 and Government Regulation No. 24 of 2005.In conducting this study, the writer uses a descriptive qualitative and quantitative research design. Interview and documentation techniques to collect data. The results of the study showed that the market levy acceptance of the 2008-2012 is very effective in the amount of 100.63% and the cost is said to be efficient levied at 7.3%. And the Department of Semarang City Market has made the process of accounting records in accordance with the Regulation of the Minister of Home Affairs No. 13 of 2006 and Government Regulation No. 24 of 2005, whereas for the preparation of financial statements in accordance with the Regulation of the Minister of Home Affairs No. 13 of 2006, financial statements were prepared on time so that it can be used for user groups to Financial Statements decision.Keywords: Revenue Performance, Recording and Reporting Process Office Market Semarang.